Lo sublime apofático y la estética neoplatónica - Papoulias, Haris; Hernández de la Fuente, David (Pontificia Universidad Católica del Perú, 2025)
The intersection between the idea of the sublime in Greek aesthetics and poetics and Neoplatonic thought at the end of Antiquity and the beginning of the Byzantine period is an important field of work yet to be investigated. This study seems to us fundamental to understand the foundations of the visual and conceptual turn that occurs between the fourth and seventh centuries in the field of philosophy of the arts and Late Antique Greek poetry, in an era marked by philosophical and aesthetic – and soon religious and political – discussion about images, their power, their representativeness and their ontological status. On this unexplored field, the present contribution aims to outline a preliminary methodology and a first approach to what we have come to call “the apophatic sublime”, as a new incipient category of study that can help to open a new way for a better understanding, at the same time, of the developments of Neoplatonic aesthetics and of the authors of Christian and pagan poetry of this period.

La intersección entre la idea de lo sublime en la estética y la poética griegas y el pensamiento neoplatónico al final de la Antigüedad y en los comienzos de la época bizantina es un importante campo de trabajo que está aún por investigar. Este estudio nos parece fundamental para entender los fundamentos del giro visual y conceptual que se produce entre los siglos IV y VII en el campo de la filosofía de las artes y la poesía griega tardoantigua, en una época marcada por la discusión filosófica y estética —y pronto religiosa y política— acerca de las imágenes, su poder, su representatividad y su estatus ontológico. Sobre este campo inexplorado, la presente contribución pretende trazar una metodología preliminar y una primera aproximación a lo que hemos dado en llamar “lo sublime apofático”, como una nueva categoría de estudio incipiente que puede ayudar a abrir una nueva vía para una mejor comprensión, a la vez, de los desarrollos de la estética neoplatónica y de los autores de poesía cristiana y pagana de esta época.
Keywords: Sublimity; Apophaticism; Byzantine Aesthetics; Late Antique Greek Aesthetics; Late Antique Greek Poetry; Sublimidad; Apófasis; Estética bizantina; Estética griega tardoantigua; Poesía griega tardoantigua; https://purl.org/pe-repo/ocde/ford#6.03.01